Regional political economy of China ascendant pivotal issues and critical perspectives - Yeoh, Emile Kok-Kheng (Institute of China Studies, University of Malaya, 2009)
This book is a collection of research papers on various pivotal issues raised by a China in the ascendant within the context of the global economy but more specifically the regional political economy of East Asia.